Transforming pulmonary embolism care: advanced catheter techniques in Pakistan: a case report - Islam, Fahad; Arif, Muhammad Sohaib; Ansari, Muhammad Imran; Hakeem, Abdul; Abubaker, Jawed (Journal of the Pakistan Medical Association, 2025)
Although post-operative acute pulmonary embolism (PE) is relatively rare, it poses a substantial risk of morbidity and mortality. We report the case of a 45-year-old hypertensive woman who presented with acute chest pain and dyspnoea eight days following a hysterectomy. On admission, she was tachycardic, hypotensive, and hypoxic. Transthoracic echocardiography revealed right ventricular dilation, a reduced tricuspid annular plane systolic excursion (TAPSE) of 12 mm, and a positive McConnell sign. Her Computed tomography pulmonary angiography confirmed bilateral pulmonary emboli. Due to a recent major surgery, systemic thrombolysis was contraindicated. Catheter-directed thrombolysis (CDT) was initiated, administering alteplase at 1 mg/hour per catheter. The patient demonstrated rapid clinical improvement, with marked reduction in oxygen and vasopressor support. She was discharged on rivaroxaban and resumed normal activities within one week. This case underscores the efficacy of CDT as a life-saving alternative in high-risk post-operative PE, especially in resource-constrained settings. Keywords: Pulmonary embolism, Thrombolysis, Echocardiography.